DEVELOPMENT OF THE BALANCED SCORECARD TO ACHIEVE QUALITY IN THE FACULTY OF ADMINISTRATIVE SCIENCES, NATIONAL UNIVERSITY OF SAN MARCOS - Narciso Gómez, Kennedy Narciso Gómez** (2015)
The Balance Scorecard (BSC), adapted to nonprofit organizations Kaplan and Norton as public management tool that will allow improving the quality of the faculty of Administrative Sciences consistent with the “Bicentennial Plan - Peru 2021” insert in the Plan Institutional Strategy 2012-2021 of San Marcos related to the strategic plan of the Faculty of Administrative Sciences 2012- 016, and the Management Model ACBSP (Accreditation Council for Business Schools and Programs), which relate to our proposal of Balance Scorecard, which objective is to achieve management in the pursuit of academic and institutional quality and deliver to society well educated graduates. In a first step, we developed the diagnosis of opportunities and needs of the Faculty of Administrative Sciences, supported by students, teachers, authorities and analyze the routing of the mission, vision and values identified in the Strategic Plan; In a second step we proceeded to develop the model of Balance Scorecard (BSC), defining the vision, mission, objectives, policies and the four perspectives: (1) learning and knowledge, (2) internal process, (3) Customer) (4) Financial; In the third stage elaborate the risk matrix and economic investment program project. Finally, consider implementing a proposed management software BSC indicators in the Faculty of Administrative Sciences of San Marcos, adapted to public organizations Kaplan and Norton as a strategic management tool, which will enable the competitiveness of the FCA-UNAC and achieve the success of its strategy to achieve its mission.